KWON3D Homepage - Kwon, Y. H.
- Mechanical Basis of Motion Analysis Coordinate Systems Cartesian Coordinates Polar Coordinates Vector & Matrix Axis Transformation Reference Frame Transformation Matrix Rotation Matrix Orientation Angles Angular Velocity--Orientation Angles Helical (Screw) Axis Mechanical Systems Motion of a Particle Position, Velocity & Acceleration Force, Mometum & Kinetic Energy Torque & Angular Momentum Dynamics of Systems of Particles Center of Mass Momentum Angular Momentum Kinetic Energy Rigid Body Dynamics Moment of Inertia & Ellipsoid of Inertia Calculation of the MOI Inertia Tensor Principal Axes Transformation of the Inertia Tensor Angular Momentum Kinetic Energy Motion in a Rotating Reference Frame Moving Reference Frame Acceleration of a Particle Acceleration of a Rigid Body System of Rigid Bodies Human Body: Linked-Segment System Center of Mass Whole Body MOI Momentum & Kinetic Energy Whole Body Angular Momentum Joint Kinetics: Joint Torque & Net Joint Force Lagrangian Dynamics Simulation of the Airborne Movement - Theories and Practice in Motion Analysis Video & Automatic Tracking Defining Reference Frames Segment Definition Local Reference Frames BSP Issues BSP Handling Strategies BSP Equations of the Geometric Shapes BSP Estimation Methods Data Processing Interpolation (Cubic Splines) Synchronization Digital Filtering User-Angles Camera Calibration DLT Method Least Square Method Modified DLT PPT (Physical Parameter Transformation) Tsai's 2-Step Camera Calibration Algorithm Panning Method Range Pole Survey Method Axis-Aligning Strategies Joint Kinetics: Joint Torque & Net Joint Force Force Plate Issues